INDEKS GINGIVITIS UNTUK ANAK BERKEBUTUHAN KHUSUS TUNAGANDA PADA SLB TUNAGANDA SAYAP IBU DI KALASAN YOGYAKARTA - Kartika Kurniasari (FKG 15 UMY 547, 2015)
Children with double disabilities need special assistance, special education and special learning device. Children with such disabilities have limited abilities to look after themselves as well as their basic needs. This also leads to a bad oral hygiene. Gingivitis is the most frequent periodontal disease that occurs in children with double disabilities. Gingivitis is a reversibel inflamation of the periodontal tissues, limited only to the gingiva that are caused by bacterias which formed by plaque. There are several ways to measure the severity and the prevalence of gingivitis, one of them is Gingival Index by Loe & Silness 1963. The aim of this study is to find out the gingivitis index for children with double disabilities in SLB Tunaganda Sayap Ibu Kalasan Yogyakarta. The design of this study is descriptive observational. This study was done in 20 students with special needs in the school by directly examining and scoring the condition of the gingiva by using the Gingival Index. The results showed that out of 20 students, 1 student (5%) has severe gingivitis, 14 students (70%) have moderate gingivitis and 5 students (25%) have mild gingivitis. No students were recorded to have a normal gingiva. Most of the students of SLB Tunaganda Sayap Ibu were experiencing moderate gingivitis. This study relevant to the hypothesis that children with double disabilities have moderate to severe gingivitis.